Pemberdayaan Masyarakat melalui Pembuatan Model Pembakaran Sampah Minim Asap di Desa Nglaris Kecamatan Bener Kabupaten Purworejo - Indah Syifa Urohmah; Ria Natali Alfarizi; Rijal Yasrif Al-Amin; Siti Lailiyah (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
Waste management at the village level still faces various challenges, particularly related to the practice of open burning, which causes environmental pollution and health risks. This condition reflects a gap between the concept of sustainable waste management within the framework of the Sustainable Development Goals (SDGs) and the social reality of local communities. This community service activity aims to implement a low-smoke waste burning container as a community-based waste management innovation and to analyze its contribution to the achievement of the SDGs in Nglaris Village. The method applied was a participatory approach involving observation, socialization, design and construction of the burning container, assistance, and program evaluation. The results indicate that the implementation of the low-smoke burning container reduces the intensity of smoke emissions, increases community participation, and encourages behavioral changes in waste management practices. The program also contributes to improving the quality of the living environment and supports the achievement of SDGs, particularly in environmental, health, and sustainable settlement aspects. These findings demonstrate that simple technological innovations adapted to local social conditions can serve as a model for sustainable waste management at the village level.